Microvascular Anatomy and Intrinsic Gene Expression of Menisci From Young Adults. Issue 13 (November 2020) - Crawford, Matthew D.; Hellwinkel, Justin E.; Aman, Zachary; Akamefula, Ramesses; Singleton, J. Thomas; Bahney, Chelsea; LaPrade, Robert F.
Background: Meniscal vascular supply is an important determinant of its healing potential. It has been reported that only the peripheral 30% of the meniscus is vascularized in cadavers aged 53 to 94 years; however, the vascularity in young patients, in whom meniscal repair is more often performed, is unknown. Purpose: The primary objective was to analyze and measure the microvascular anatomy of the meniscus in adult cadaveric specimens <35 years old. The secondary objective was to assess angiogenic potential by quantifying regional gene expression in a meniscal allograft cohort <45 years old. Study Design: Descriptive laboratory study. Methods: In part 1 of this study, 13 fresh-frozen cadaveric knees (age range, 22-34 years; mean, 28.5 years) underwent popliteal artery India ink injection and tissue clearing using a Spalteholz technique, followed by microvascular vascular measurement. In part 2, mRNA was isolated from 13 meniscal allografts (age range, 17-43 years; mean, 27.2 years), and expression of angiogenic genes, vascular endothelial growth factor ( VEGF ), and vascular endothelial growth factor receptor 1 ( FLT1 ) was quantified using real-time polymerase chain reaction. Results: The maximal depth of vascular penetration into the periphery of the medial and lateral menisci ranged from 0% to 42% and 0% to 48%, respectively. There was variation in the degree of vascular penetration within the medial meniscus, with the posterior horn having a significantly smaller depth of penetration (median, 8.7%) than that of the anterior horn (median, 17.4%; P < .0001) or midbody (median, 17.5%; P = .0003). There were no differences in angiogenesis gene expression ( VEGF / FLT1 ) based on circumferential or radial meniscal locations. Conclusion: The vascular supply of the medial and lateral menisci in specimens from adults <35 years of age extended farther than what was reported in specimens from older individuals; however, median values remained consistent. Gene expression of the angiogenic marker VEGF was low throughout all regions of uninjured menisci from young adults, which is consistent with reports in older specimens. Clinical Relevance: Improved understanding of meniscal vascular supply in young adults is critical to informing clinical treatment decisions.